Zakat Melalui FinTech: Analitik Literatur Perspektif Hukum Ekonomi Islam - Muhammad Alfarizi (Jurnal Kawakib, 2023)
The COVID-19 pandemic and the resulting economic restrictions have adversely affected individuals and communities. One potential solution is to use zakat to support public welfare. However, the pandemic's initial phase led to a decrease in the collection of zakat funds. Fortunately, the emergence of FinTech has facilitated an increase in zakat collection. This study examines the payment of zakat through FinTech from the perspective of Islamic Sharia Law. Utilizing scientific literature analysis and Al-Quran studies, the findings suggest that paying zakat through FinTech is not prohibited. The various digital zakat facilities available have the potential to motivate people to pay their zakat to institutions, particularly during the pandemic. To maximize the efficiency and effectiveness of FinTech in increasing the volume of zakat payments, we recommend that three interested parties take certain steps, which will be conveyed later. Using FinTech for zakat payments can help alleviate the pandemic's impact on public welfare.